APPLICATIONS OF TALENT MANAGEMENT IN THE TRAVEL AND TOURISM SECTOR : A SYSTEMATIC REVIEW OF THE LITERATURE - Pringgabayu, Dematria; Dewi, Emilia Fitriana; Hapsari, Ayuningtyas Yuli; Silvianita, Anita (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
The fourth industrial revolution's revolutionary changes to the business environment and skill sets, along with increased global mobility, global demographic and economic trends, and a more diverse workforce, are creating the ideal storm for strategic human resource management (SHRM). A tough corporate climate that requires constant advancement and innovation has been identified as the hallmark of the knowledge-based economy. Organizations' capacity is significantly impacted by the caliber of knowledge they apply to succeed in the increasingly competitive knowledge-based market economy. The methodologies of this study employed the traditional Systematic Literature Review (SLR), which compiled some previous studies to be examined. The initial studies were only selected from the article published in a reputable journal indexed by Scopus. Of the 207 reviewed articles, 31 articles were selected to be included in the analysis. Talent management is the methodical planning, acquisition, development, performance management, engagement, and retention of workers who have been identified as having talent within the company. In order to establish an evidence-based comprehensive multilevel framework, this review intends to compile empirical evidence on the components of talent management. The crucial components are talent management practices, determinants, and results. This evaluation attempts to describe the majority of talent management practices as well as the best suggestions for enhancing talent management in the tourism industry